100 contemporary wood buildings - Jodidio, Philip, ....- (Köln : Taschen, 2015)
Not so very long ago, some might have considered wood a material of the past, long since replaced by more modern components such as concrete and steel. The truth is radically different. Bolstered by new manufacturing techniques and ecological benefits, wood has seen a fabulous resurgence in contemporary construction. This Bibliotheca Universalis edition explores how architects around the world have created and invented with this elementary material. Featuring follies, very large buildings, and ambitious urban renewal schemes, it celebrates the diverse deployment of wood by architects around the world. We see how wood can at once transform urban spaces, as in the Metropol Parasol in Seville by Jurgen Mayer H., and allow for sensitive interventions in natural environments, such as at the Termas Geometricas Hot Springs Complex in Pucon, Chile, by German del Sol. True to all TASCHEN architecture titles, the book pays tribute to many emerging international talents as well as to such renowned figures as Tadao Ando and Renzo Piano. It celebrates each architect's vision and innovation, as well as investigating the techniques, trends, and principles that have informed their work with wood. It examines the computer-guided milling that has allowed for novel new forms, the responsible harvesting that allows wood to align with our environmental concerns, and, above all, wood's enduring appeal to our senses and psyche, comforting hectic modern lives with a sense of Arcadian simplicity. From a functional tree house to inspired restaurants, this collection instructs on the ecology of wooden construction, with plenty of eye candy for architecture enthusiasts. - TIME, New York.
Engels, Duits, Frans
Keywords: Architectuur ; hout